Antimicrobial Susceptibility Trends Observed in Urinary Pathogens Obtained From New York State. (16th November 2018) - Rank, Elliot L; Lodise, Thomas; Avery, Lisa; Bankert, Eve; Dobson, Erica; Dumyati, Ghinwa; Hassett, Stephen; Keller, Marina; Pearsall, Matthew; Lubowski, Teresa; Carreno, Joseph J
Abstract: International guidelines recommend using local susceptibility data to direct empiric therapy for acute uncomplicated cystitis. We evaluated outpatient urinary isolate susceptibility trends in New York State. Nitrofurantoin had the lowest resistance prevalence whereas trimethoprim-sulfamethoxazole and fluoroquinolones had higher prevalences. This study highlights the need for local outpatient antimicrobial stewardship programs.